Evaluating dysphagia in Alzheimer’s disease: the significance of age and medical comorbidities,a cross-sectional study from a tertiary psychiatric hospital in Guangzhou China - Ye, Junrong; Pan, Yuanxin; Zhou, Tingwei; Liu, Fei; Wei, Yanheng; Chen, Jiao; Wang, Wen; Zheng, Xueyu; Liu, Dingjie; Wu, Shengwei; Li, Zezhi; Guo, Jianxiong; et al. (Frontiers in Psychiatry, 2024)
Objective To investigate the influencing factors of dysphagia in Alzheimer’s disease (AD) patients. Methods The study evaluated the demographic characteristics, nutritional status, social functioning, and swallowing dysfunction of 109 hospitalized AD patients. Results The sample include 65.1% of female patients, mainly concentrate in >70 years old (72.5%). The illness duration is mainly 0 5 years (62.4%). After adjusting for confounding factors such as gender, poor lifestyle habits, illness duration, marital status, route to admission, concomitant medical illness, nutritional status, and social functioning, we find that the swallowing function in patients with AD is related to route to admission and concomitant medical illness (mainly includes: circulatory disease and respiratory disease). Age ≥90 years old and more concomitant medical illness contribute to a lower swallowing dysfunction score in patients with AD (P<0.05). Conclusion Age and concomitant medical illness are the important influencing factors in swallowing dysfunction in patients with AD. Therefore, we believe that future research should focus on the treatment and care of patients with medical conditions in order to enhance the swallowing function in patients with AD.